+0  
 
0
57
1
avatar+1159 

Help.

NotSoSmart  Nov 16, 2017
Sort: 

1+0 Answers

 #1
avatar+79894 
+1

y = -x^2 + 12x - 4

 

We need to complete the square, NSS

 

Factor out the negative

 

y = - ( x^2 - 12x + 4)

 

Take 1/2 of -12  = -6   square it  = 36....add it and subtract it inside the parentheses

 

y = - (x^2 - 12x + 36 + 4 - 36)     factor the first three terms, simplify the rest

 

y = - [  ( x - 6)^2  - 32 ]      apply the negative back across the terms

 

y =  - (x - 6)^2  + 32

 

In the form, y = a (x - h)^2 + k   the vertex is (h, k)  =  ( 6 , 32 )

 

 

cool cool cool

CPhill  Nov 16, 2017

24 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details